2020
DOI: 10.1016/j.celrep.2020.03.079
|View full text |Cite
|
Sign up to set email alerts
|

AMPAR Auxiliary Protein SHISA6 Facilitates Purkinje Cell Synaptic Excitability and Procedural Memory Formation

Abstract: Highlights d SHISA6 is prominently expressed in Purkinje cells in close association with AMPARs d SHISA6 absence in Purkinje cells results in impaired procedural memory formation d Purkinje cell synaptic baseline excitatory transmission is facilitated by SHISA6 d Purkinje cell AMPAR kinetics are modulated by SHISA6

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 52 publications
(76 reference statements)
2
14
0
Order By: Relevance
“…Notably, Shisa7 (CKAMP59) has emerged as an interesting member of the Shisa family in that unlike other CKAMP counterparts, Shisa7 has a direct role in GABA A R regulation at inhibitory synapses ( Han et al, 2019 ). While other CKAMPs are localized at glutamatergic synapses ( von Engelhardt et al, 2010 ; Klaassen et al, 2016 ; Peter et al, 2020 ), we observed that Shisa7 co-localizes specifically with gephyrin and GABA A Rs in hippocampal neurons ( Han et al, 2019 ) and not at excitatory synapses as reported in an earlier study ( Schmitz et al, 2017 ). Functionally, Shisa7 regulated GABA A R trafficking and inhibitory transmission without affecting excitatory synaptic transmission ( Han et al, 2019 ).…”
Section: Recent Advances In Gaba a R Biologysupporting
confidence: 83%
“…Notably, Shisa7 (CKAMP59) has emerged as an interesting member of the Shisa family in that unlike other CKAMP counterparts, Shisa7 has a direct role in GABA A R regulation at inhibitory synapses ( Han et al, 2019 ). While other CKAMPs are localized at glutamatergic synapses ( von Engelhardt et al, 2010 ; Klaassen et al, 2016 ; Peter et al, 2020 ), we observed that Shisa7 co-localizes specifically with gephyrin and GABA A Rs in hippocampal neurons ( Han et al, 2019 ) and not at excitatory synapses as reported in an earlier study ( Schmitz et al, 2017 ). Functionally, Shisa7 regulated GABA A R trafficking and inhibitory transmission without affecting excitatory synaptic transmission ( Han et al, 2019 ).…”
Section: Recent Advances In Gaba a R Biologysupporting
confidence: 83%
“…Our finding that in the KO model, GC activity patterns promote faster learning than MF inputs only for high levels of MF activity might thus explain the discrepancy between spared locomotion and absence of associative learning in GluA4-KO mice. These results are in line with previous studies, where impairments of MF→GC or PF→PC synapses did not cause locomotion defects but affected motor learning ( Andreescu et al, 2011 ; Galliano et al, 2013 ; Peter et al, 2020 ; Seja et al, 2012 ). Indeed, a small number of active GCs may be sufficient for basic motor performance ( Galliano et al, 2013 ; Schweighofer et al, 2001 ).…”
Section: Discussionsupporting
confidence: 93%
“…Several previous studies investigated PF→PC synaptic function and plasticity in cerebellum-dependent motor learning ( Galliano et al, 2013 ; Grasselli et al, 2020 ; Gutierrez-Castellanos et al, 2017 ; Peter et al, 2020 ; Wada et al, 2007 ). Afferent sensory information to the cerebellar cortex is first processed at the upstream MF→GC synapse ( Billings et al, 2014 ; Cayco-Gajic et al, 2017 ), which may support cerebellar learning.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies investigated PF→PC synaptic function and plasticity in cerebellum-dependent motor learning (Galliano et al, 2013; Grasselli et al, 2020; Gutierrez-Castellanos et al, 2017; Peter et al, 2020; Wada et al, 2007). Afferent sensory information to the cerebellar cortex is first processed at the upstream MF→GC synapse (Billings et al, 2014; Cayco-Gajic et al, 2017), which may contribute to cerebellar learning.…”
Section: Discussionmentioning
confidence: 99%